Effects of ischaemic conditioning on tissue oxygen saturation and heart rate variability: an observational study. Issue 7 (July 2019) - Cho, Youn Joung; Lee, Hyung-Chul; Choi, Eue-Keun; Park, Seoyeong; Yu, Je Hyuk; Nam, Karam; Kim, Tae Kyong; Jeon, Yunseok
Objective: Ischaemic conditioning (IC) has organ-protective effects, but its clinical results have been inconsistent. Tissue oxygen saturation (StO2 ) and heart rate variability (HRV) reflect peripheral microcirculation and autonomic nervous system activity, but their changes during IC have not been well documented. We assessed StO2 and HRV during IC in patients undergoing cardiac surgery and healthy volunteers. Methods: Ten patients undergoing cardiac surgery and 10 healthy male volunteers underwent remote IC (four 5-minute cycles of ischaemia/reperfusion) applied to the upper arm. Changes in StO2 at the thenar eminence and HRV according to the R-R intervals were recorded during IC. Results: The lowest StO2 during ischaemia significantly decreased in patients and significantly increased in volunteers. Among the HRV parameters, the low-frequency domain, which corresponds to sympathetic activity, significantly increased after IC in volunteers but not in patients. Other variables were similar between the groups. Conclusions: These results suggest that the minimum tissue oxygen content is depleted during ischaemia in patients and preserved in healthy volunteers. Sympathetic nervous activity seems to increase after IC in healthy volunteers but remains unaffected in patients. Thus, IC may act differently between patients undergoing cardiac surgery and healthy subjects.